The Annotated Luther: Updating His Essential Writings. Issue 2 (June 2017) - Tunseth, Scott
Abstract: This article provides a summary of how The Annotated Luther series was conceived and developed to reach a broad readership for a new generation of students of Luther and the Reformation. Included is a brief history of the project and the editorial principles that have guided the translation of Luther's writings, as well as the supporting annotations, introductions, and images.